Ultrastructure of the seminal vesicles after chronic hyperthermia exposure in experiment - Pastukhova , V.A.; Lukyantseva , H.V.; Krasnova , S.P. (Морфологія / Morphologia / Morfologìâ, 2025)
Background. The increasing prevalence of male infertility highlights the importance of studying factors that disrupt the morphofunctional state of accessory sex glands. Heat stress is considered a key pathogenic factor capable of impairing reproductive function at cellular and subcellular levels. Despite extensive data on the effects of hyperthermia on spermatogenesis, ultrastructural changes in seminal vesicles remain insufficiently characterized. Objective. To determine the ultrastructural features of seminal vesicles in rats after chronic whole-body hyperthermia. Methods. The study was conducted on sexually mature male albino rats exposed to hyperthermia at 39.6–40.9°C for 5 hours daily over 60 days. Tissue samples were collected immediately after the experiment. Ultrastructural analysis was performed using transmission electron microscopy with standard fixation, dehydration, embedding, and contrasting procedures. Results. Marked epithelial damage was observed, including plasma membrane disintegration, reduction of biosynthetic organelles, mitochondrial injury, decreased Golgi cisternae, and secretory granule loss. Cytoplasmic clearing, heteromorphism of epithelial cells, and increased lysosomes and phagosomes indicated enhanced autolytic activity. Cells with necrotic and pro-apoptotic features were identified. The submucosa exhibited fibrosis, edema, and impaired microcirculatory integrity with hypoxic signs. Conclusion. Chronic hyperthermia induces profound ultrastructural remodeling of seminal vesicles characterized by membrane disruption, organelle damage, reduced secretory capacity, and microcirculatory disorders. These changes reflect morphological mechanisms underlying the decline in seminal vesicle function in response to heat stress.